The Incompleat Sound Operator: A Brief Compendium of Recommendations, Tips and Techniques for Sound System Operators at Live Music Performances That Use Sound Reinforcement - Kennedy, Ridge (Hedgehog House, 2020)
A "how-to" book for people who operate sound systems that covers all aspects of "doing sound." It includes information about pre-event planning, setup, and operation. It covers gain structure (getting the volume right) mixing and sound equalization. There are recommendations and tips for all aspects of sound operation. Also it includes a visual glossary.